2011
DOI: 10.1002/jtr.852
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Regional Food Festivals for Destination Branding

Abstract: This paper investigates the role of regional food festivals for destination branding and explores the characteristics of regional food festivals that contribute to building a destination brand. It was found that regional food festivals can play a decisive role for destination branding. Activities using local food and activities promoting the regions' attractions were suggested to be offered by food festivals for enhancing the impact of festivals for destination branding and improving the positive image of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
113
0
15

Year Published

2012
2012
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(140 citation statements)
references
References 26 publications
3
113
0
15
Order By: Relevance
“…Food festivals and events contribute to regional development [74] and regional destination branding, benefitting producers and local businesses not only by attracting locals and visitors but also by increasing awareness of a particular area as a destination by showcasing its local food [75].…”
Section: Celebrating the Local: Food Events And Festivalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Food festivals and events contribute to regional development [74] and regional destination branding, benefitting producers and local businesses not only by attracting locals and visitors but also by increasing awareness of a particular area as a destination by showcasing its local food [75].…”
Section: Celebrating the Local: Food Events And Festivalsmentioning
confidence: 99%
“…Food tourism is part of the cultural tourism market [77] within the experience economy framework and a major area of interest for regions, particularly rural ones [75]. In the experience economy, "while commodities are fungible, goods tangible and services intangible, experiences are memorable" [78] (p. 11).…”
Section: Food Tourismmentioning
confidence: 99%
“…Previous research has identified that regional food manifestations can play an important role not only in economic development (du Rand, et al, 2003;du Rand, Heath, 2006) but also in the development of regional tourism, adding value to already existing products (Quan, Wang, 2004). In addition, food manifestations are used as the promotion of local facilities and differ from manifestations of metropolitan communities (Cela, et al, 2007;Sharples, 2008;Lee, Arcodia, 2011;Kalenjuk, et al, 2012a;Kalenjuk, et al, 2012b).…”
Section: Introductionmentioning
confidence: 99%
“…Özellikle son zamanlarda, araştırmacılar tarafından destinasyon markalaşmasında festivallerin etkisine yoğun bir şekilde dikkat çekildiği gözükmektedir (Chalip ve Costa, 2005;Lee ve Arcodia, 2011;Crockett ve Wood, 1999). Festivaller yörenin özel günlerine ya da kültürel unsurlarına odaklanılarak gerçekleştirilebildiği gibi sadece tek bir ürüne odaklanılarak da gerçekleştirilmektedir.…”
Section: Introductionunclassified